More than a Question of Agency: Privatized Project Implementation, Accountabilities, and Global Environmental Governance. Issue 1 (January 2017) - Rosenberg, Jonathan
Abstract: With limited success, international relations scholars have used principal‐agent theory (P‐A) to understand gaps in global governance. While P‐A may not provide robust explanations, it is still useful for mapping long chains of complex, boundary‐crossing relationships and locating the gaps that characterize global environmental governance (GEG). In this article, first I argue that we can get beyond merely locating and describing governance gaps, and start explaining them, by considering the problems of accountability that contribute to those gaps. Second, I argue that outsourced sustainable development projects, implemented by for‐profit contractors, provide an under‐studied and under‐theorized body of cases for examining the relationship between agency and accountability. Finally, I use the example of a United States Agency for International Development post‐hurricane recovery project in Grenada to suggest that when development assistance agencies privatize implementation they prioritize more economistic logics of accountability. As a result, they may enhance short‐term economic efficiency and even become more accountable to their principals. But they fail to connect the means and ends of GEG, despite firmly stated, official commitments to "taking the environment into account."